2023
DOI: 10.5109/6782154
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Electrospinning Precursor Flow Rate with Rotating Collector on ZnO Nanofiber Size Results on Double-Layered DSSC Photoanode Fabrication

Abstract: DSSC solar cells are predicted to be energy conversion devices for the next generation; therefore, various developments are carried out to improve the performance of DSSC solar cells. In this paper, we present the results of research on the process of using ZnO nanofibers as DSSC photoanodes using an electrospinning machine. The direct deposition method was used to directly spray the ZnO precursor solution on conductive glass deposited with TiO2. The rotating collector was used to make uniform and reduce the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
1
0
Order By: Relevance
“…For Li-ion batteries, the electrode must be designed with precise electrospinning parameters to attain high capacity, fast charging rates, and long cycle life [94] . Electrospinning technique has also been found competent for designing nanofibers for dye-sensitized solar cells for high efficiency [95] . Some significant designs of inorganic or metal-organic hybrid based electrospinning nanofibers have been applied for high performance gas sensing and chemiresistive sensing devices [96,97] .…”
Section: Applications Of Nanocomposite Nanofibers and Membranes Prepa...mentioning
confidence: 99%
“…For Li-ion batteries, the electrode must be designed with precise electrospinning parameters to attain high capacity, fast charging rates, and long cycle life [94] . Electrospinning technique has also been found competent for designing nanofibers for dye-sensitized solar cells for high efficiency [95] . Some significant designs of inorganic or metal-organic hybrid based electrospinning nanofibers have been applied for high performance gas sensing and chemiresistive sensing devices [96,97] .…”
Section: Applications Of Nanocomposite Nanofibers and Membranes Prepa...mentioning
confidence: 99%
“…Yarin and Reneker reported that process control of electrospinning resulted in fibers with nanoscale diameters [22]. The morphology and diameter of the obtaining nanofibers depend on polymer properties and parameters processes, such as polymer molecular weight, solvent, applied voltage, solution viscosity, needle diameter, and needle tip distance to collector [23,24]. The working principle of comprehensive electrospinning has been discussed in another paper [25].…”
Section: Introductionmentioning
confidence: 99%